Correlation of Acid-Base Status with Mortality of Neonates Admitted in PICU - Hoque, Md Shafiul; Sarkar, Prabir Kumar (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: The human organs and tissues function under a tightly controlled pH in the range of 7.35 to7.45. Depending on the degree of deviation of pH outside this narrow range, several homeostatic responses are activated in an effort to restore normal acid-base status. Objectives: To study the acid-base disturbances in neonates admitted in PICU. Methods: This study was conducted in Pediatric Intensive Care Unit (PICU) of Dhaka Shishu (Children) Hospital for a period of six monthsfrom January to June 2018. Hundred neonates attending pediatric emergency services with various ailments were curolled. Arterial blood gas (ABG) analysis was estimated in these neonates. Ethical committee approval was taken. Results: Metabolic acidosis was the most common acid-base disorder. Fifty-seven neonates had metabolic acidosis.Significant correlation was observed between metabolic acidosis and pathological conditions like birth asphyxia and sepsis. Conclusion: Metabolic acidosis is the most common acid base disorder in critically ill neonates.In this study it was the most common cause of mortality. If we do earlyintervention in correction of acid-base abnormality, the outcome is likely to get improved in neonates. DS (Child) H J 2019; 35(1) : 37-41